Characterization of an hrp-aox-polyaniline-graphite composite biosensor - Ana Carolina O. Santana; Erica F. Southgate; João Paulo B. G. Mendes; Jo Dweck; Eliana Mosse Alhadeff; Ninoska Isabel Bojorge Ramirez (Journal of Electrochemical Science and Engineering, 2014)
Nowadays there is an increasing demand to develop new and robust biosensors in order to detect low concentrations of different chemicals, in practical and small devices, giving fast and confident responses. The electrode material was a polyaniline-graphite-epoxy composite (PANI/GEC). Alcohol oxidase (AOX) and horseradish peroxidase (HRP) enzymes were immobilized and the responses were tested by cyclic voltammetry. The conductivities for the composites of graphite/polyaniline were determined. The cyclic voltammograms allowed detecting ethanol in pure diluted samples in a range from 0.036 to 2.62 M. Differential scanning calorimetry (DSC) and thermal gravimetry analysis (TGA) were used to verify the thermal characteristics of the composites (0, 10, 20, 30 and 100 % of graphite). The Imax value was determined for the dual enzyme biosensor (0.0724 mA), and the Kapp m  as 1.41 M (with R2 =0.9912).